Audio-visual learning for the prevention of bloodstream infections in hemodialysis patients with double-lumen catheters: A literature review - Widyanti, Feranema; Haryanto, Haryanto; Suriadi, Suriadi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Chronic Kidney Disease (CKD) with Double Lumen Cahthter Hemodialysis therapy requires comprehensive education to improve patient knowledge of CDL care. Technological developments enable digital-based education to be an effective solution in improving patient understanding. Purpose: To examine the effectiveness of digital video-based education in improving mental health outcomes and infection prevention behaviors among hemodialysis patients with double lumen catheters. Method: A literature review by analyzing 20 articles from various databases such as Google Scholar, Science Direct, Scopus, Elsevier, and PubMed. Results: The use of digital applications as educational media, such as educational videos, Pocket Book Application, EMALA-LISA and Hellodialisa, significantly improve patient understanding of aspects of self-care, diet, and symptom management. Conclusion: Educational videos have proven effective in improving knowledge about CDL care in CKD patients undergoing hemodialysis therapy. Keywords: Double Lumen Catheter Care; Educational Video; Hemodialysis; Infection Prevention Behavior.